Policy Analysis for the Operation of Cianjur State Community Academy - Wati Karmila (International Journal of Nusantara Islam, 2019)
This study aims to determine the suitability of the study program at the Community Academy for the potential of the region and to know the interest of secondary school graduates continuing to the Community Academy. The research method used is a qualitative method with a descriptive approach. The data and information in this study were collected through Focuss Group Discussion (FGD) and questionnaires. The conclusion in this study is that the Community Academy study program in the city of cianjur is still not in accordance with regional potential, because the study program only represents the needs of the workforce in general and the Cianjur City Community Academy gets considerable interest from secondary school graduates.